Comprehensive safety evaluation of isatuximab in multiple myeloma using disproportionality analysis of FAERS and meta-analysis of randomized controlled trials - Muhammed Favas Karimbanathottathil; Beema T Yoosuf; M Mamatha; Dipika Bansal (Scientific Reports, 2024)
Abstract Isatuximab, an anti-CD38 monoclonal antibody, has been shown to induce apoptosis in multiple myeloma (MM) cells and is effective in both relapsed/refractory and newly diagnosed MM cases. This study aims to compare the safety profile of isatuximab by examining a broader range of adverse events (AEs) using data from the FDA Adverse Event Reporting System (FAERS) and a meta-analysis of randomized controlled trials (RCTs). The study analyzed FAERS data up to March 2024, identifying suspected AEs using Preferred Terms. Data extraction from FAERS was conducted using OpenVigil-2.1-MedDRA-v24. Disproportionality analysis was performed by calculating the proportional reporting ratio (PRR) with Chi-square value, and the reporting odds ratio (ROR) with a 95% confidence interval (CI). For the meta-analysis, safety outcomes of isatuximab in adult patients were reviewed from RCTs sourced from databases such as PubMed, EMBASE, and ClinicalTrials.gov, employing a random-effects meta-analysis to determine the risk ratio (RR) with 95% CI. The meta-analysis protocol was registered with PROSPERO (CRD42022379632). Based on the FAERS quarterly reports, a total of 2,325 AE reports were identified, with a higher incidence in men (n = 1156, 49.7%) compared to women (n = 960, 41.3%). AEs commonly observed with isatuximab therapy included neutropenia, pneumonia, infusion-related reactions, thrombocytopenia, acute kidney injury, and anemia. In our meta-analysis of three RCTs involving 1,258 patients, 659 (52.4%) in the isatuximab treatment group experienced 1,135 AEs, with 58% classified as grade three or higher. In comparison, 599 (47.6%) patients in the control group reported 906 AEs, with 59% categorized as grade three or higher. Notably, the isatuximab group showed a statistically significant increased risk of grade three or higher neutropenia (RR = 2.13, 95% CI: 1.12–4.03, p = 0.0207) and a 30% increased risk of grade 3 or higher thrombocytopenia (RR = 1.30, 95% CI: 1.03–1.64, p = 0.0244). Isatuximab therapy was generally well-tolerated and exhibited a manageable safety profile. Considering these findings, future research might benefit from longer follow-up periods to capture delayed and less frequent AEs.